1995
DOI: 10.1099/0022-1317-76-11-2669
|View full text |Cite
|
Sign up to set email alerts
|

Domains of the Epstein--Barr virus nuclear antigen 2 (EBNA2) involved in the transactivation of the latent membrane protein 1 and the EBNA Cp promoters

Abstract: The Epstein-Barr virus (EBV) nuclear antigen 2 (EBNA2) is one of the first EBV-encoded gene products expressed after infection of primary B lymphocytes. EBNA2 is essential for the growth-transforming potential of the virus and it functions as a transcriptional activator of a set of viral and cellular genes. Sequencespecific DNA-binding by EBNA2 has not been demonstrated but the molecule is targeted to specific DNA regions by a cellular protein, RBP-JK, which recognizes the GTGGGAA sequence present in the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 51 publications
0
49
0
Order By: Relevance
“…essential for EBV's hallmark function, growth transformation of B lymphocytes (21,35,36). The finding that IRF7 induces expression of LMP1 provides a possible partial explanation for how LMP1 is expressed, although at low levels, in type II cells in the absence of EBNA2 (28) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…essential for EBV's hallmark function, growth transformation of B lymphocytes (21,35,36). The finding that IRF7 induces expression of LMP1 provides a possible partial explanation for how LMP1 is expressed, although at low levels, in type II cells in the absence of EBNA2 (28) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The other two pathways, ubiquitination and CDC42 activation, are mediated by LMP1 N-terminal and transmembrane domains, respectively (reviewed in references 9 and 20). Induction of expression of LMP1 depends on several virus-specific factors, the best characterized of which is the transcriptional activator EBV nuclear antigen 2 (EBNA2) (16,34,35,38,40).Our previous work uncovered the intimate involvement of IRF7 in EBV latency and showed first that IRF7, along with IRF2, represses the promoter used for expression of EBNA1 in type I latency in which latent gene expression is most restricted (45). We then detailed a special relationship between IRF7 and LMP1, which is capable of both inducing expression of and activating IRF7 (46, 49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The transforming ability of LMP1 is tightly linked to its association with the tumor necrosis factor family receptor-associated factors and may function similarly to the tumor necrosis factor family receptor, aggregating in the plasma membrane, where it is capable of binding tumor necrosis factor family receptor-associated factors (15,48). Numerous studies of LMP1 regulation have demonstrated that expression of LMP1 is dependent on regulation of its promoters by viral and cellular transcription factors (20,21,30,42,64,65,76).…”
mentioning
confidence: 99%
“…EBNA2 lacks the ability to directly bind DNA but targets and activates EBV promoter elements through its association with RBP-J and other cellular transcription factors, including PU.1 and AML1 (21,23,30,42,(64)(65)(66)81). EBNA2 also associates with the basal transcription machinery and other coactivators of transcription and has been shown to transactivate the major EBV latent promoters and other responsive cellular promoters (73)(74)(75).…”
mentioning
confidence: 99%